2021
DOI: 10.1016/j.jcmgh.2021.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Luminal Control of Intestinal Macrophage Maturation in Patients With Ulcerative Colitis During Remission

Abstract: Fecal luminal factors from ulcerative colitis patients in remission, unlike from healthy individuals, fail to induce macrophage hyporesponsiveness, a feature typical of intestinal macrophages. This suggests a role for fecal luminal factors in guiding macrophage maturation under physiological conditions and disease. BACKGROUND & AIMS:Intestinal macrophages adopt a hyporesponsive phenotype through education by local signals. Lack of proper macrophage maturation in patients with ulcerative colitis (UC) in remissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
5
10
0
Order By: Relevance
“…Interestingly, fecal supernatants had a suppressive effect on cytokine secretion of colonoid monolayers as compared to PBS (negative control) and LPS (positive control). This is in line with a previous study of our group, where macrophages showed reduced cytokine production after conditioning with fecal supernatants as compared to untreated cells 47 . Altogether, our results sustain the concept of the intestinal microenvironment educating the host to stay unresponsive to the load of bacterial stimuli constantly present in the gut to maintain homeostasis 47 …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, fecal supernatants had a suppressive effect on cytokine secretion of colonoid monolayers as compared to PBS (negative control) and LPS (positive control). This is in line with a previous study of our group, where macrophages showed reduced cytokine production after conditioning with fecal supernatants as compared to untreated cells 47 . Altogether, our results sustain the concept of the intestinal microenvironment educating the host to stay unresponsive to the load of bacterial stimuli constantly present in the gut to maintain homeostasis 47 …”
Section: Discussionsupporting
confidence: 93%
“…This is in line with a previous study of our group, where macrophages showed reduced cytokine production after conditioning with fecal supernatants as compared to untreated cells. 47 Altogether, our results sustain the concept of the intestinal microenvironment educating the host to stay unresponsive to the load of bacterial stimuli constantly present in the gut to maintain homeostasis. 47 The fecal microbiota profiles differed between IBS patients and healthy subjects.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Fecal supernatant aliquots were stored at À80°C for future use. 20 Rat treatments and fecal transplantation experiments. To elucidate the contribution of gut microbiota to CAL establishment, we performed FMT experiment in rat models.…”
Section: Methodsmentioning
confidence: 99%
“…An increasing volume of evidence shows that macrophages play an important role in the pathogenesis and persistence of UC. It has been reported that macrophage polarization and changes in related signaling pathways have protective effects against intestinal inflammation ( De Schepper et al, 2018 ; Maasfeh et al, 2021 ). Macrophages can be transformed into classically activated (M1) macrophages or alternatively activated (M2) macrophages according to different environmental stimulus responses.…”
Section: Introductionmentioning
confidence: 99%